Quantum entanglement in nanocavity arrays - Liew, Timothy Chi Hin (2017)
We show theoretically how quantum interference between linearly coupled modes with weak local nonlinearity allows the generation of continuous variable entanglement. By solving the quantum master equation for the density matrix, we show how the entanglement survives realistic levels of pure dephasing. The generation mechanism forms a paradigm for entanglement generation in arrays of coupled quantum modes.